A prospective, randomized, double-blind, placebo-controlled trial of acute postoperative pain treatment using opioid analgesics with intravenous ibuprofen after radical cervical cancer surgery - Liu, Xintong (Sci Rep, 2018)
This study assessed the efficacy and tolerability of intravenous ibuprofen in the improvement of post-operative pain control and the reduction of opioid usage. Patients were randomly divided into placebo, ibuprofen 400 mg and ibuprofen 800 mg groups. All patients received patient-controlled intravenous morphine analgesia after surgery. The first dose of study drugs was administered intravenously 30 min before the end of surgery and then every 6 hours, for a total of 8 doses after surgery. The primary endpoint of this study was the mean amount of morphine used during the first 24 hours after surgery. Morphine use was reduced significantly in the ibuprofen 800 mg group compared with the placebo group (P = 0.04). Tramadol use was reduced significantly in the ibuprofen 400 mg and ibuprofen 800 mg groups compared with the placebo group (P < 0.01). The area under the curve of visual analog scale pain ratings was not different between groups. Safety assessments and side effects were not different between the three groups. Intravenous ibuprofen 800 mg was associated with a significant reduction in morphine requirements, and it was generally well tolerated for postoperative pain management in patients undergoing radical cervical cancer surgery.